Can the Baidu Index predict realized volatility in the Chinese stock market? - Wei Zhang; Kai Yan; Dehua Shen (Financial Innovation, 2021)
This paper incorporates the Baidu Index into various heterogeneous autoregressive type time series models and shows that the Baidu Index is a superior predictor of realized volatility in the SSE 50 Index. Furthermore, the predictability of the Baidu Index is found to rise as the forecasting horizon increases. We also find that continuous components enhance predictive power across all horizons, but that increases are only sustained in the short and medium terms, as the long-term impact on volatility is less persistent. Our findings should be expected to influence investors interested in constructing trading strategies based on realized volatility.
Keywords: 650; Baidu Index; Chinese stock market; HAR model; Realized volatility